An Environmental Impact Framework for Evaluating Construction Projects Delays - Ansah, Richard Hannis; Sorooshian, Shahryar; Shariman, Mustafa; Duvvuru, Gomanth (IEOM Society, 2016)
The modern business environment is operating in a highly turbulent time. Demand for operational activities to achieve effectiveness and efficiency, the environment has increased the need for organizational accountability both in private and public sectors. Meanwhile, one noteworthy gap in the management of projects is considering projects as systems existing in isolation from its surrounding environment. From an examination of the deficiencies in such an approach and how to avoid them, an understanding of the concept of the environment is very imperative. Besides, while many variables are said to cause process and system delays in construction projects, most have been conceptualized to assess aspects of project delays. However, most of these variables for assessing project delays still need improvement. This paper presents the concept of project environment, and proposes a comprehensive framework for evaluating delay sources in the external environment of construction projects through ‘PESTLE’ Framework Analysis namely; Political, Economic, Social, Technological, Legal and Environmental. Following the synthesis and screening of the literature review and the identified main sources, it showed that the major external sources of delays are associated with the ‘PESTLE’ factors. Thus, it is therefore established that ‘PESTLE’ framework analysis, if well understood, could be an instrumental tool for project performance assessment studies and contributes to the knowledge and practice on delay control.